It’s Time to Revisit the Cairo Consensus - Christopher Tucker (The White Horse Press, 2021)
Just over a quarter century ago, the so-called ‘Cairo Consensus’ was forged, fundamentally improving how governments worldwide, international organisations, and the NGO community approached women’s reproductive health and reproductive rights on the world stage. Yet, the deafening silence this consensus offered on issues of runaway population growth has had massive repercussions on the world we live in today, with the ever-increasing human footprint fuelling climate change and ecological destruction on a scale that was entirely predicted. Given what we know now about how empowering, just and ethical strategies focused on women and girls can effectively bend the global population curve, it is time that we revisit the Cairo Consensus.